2017
DOI: 10.1521/aeap.2017.29.2.154
|View full text |Cite
|
Sign up to set email alerts
|

An Event-Level Analysis of the Interpersonal Factors Associated With Condomless Anal Sex Among Gay, Bisexual, and Other Men Who Have Sex With Men (MSM) With Online-Met Partners

Abstract: The interpersonal determinants of condomless anal sex (CAS) within online-initiated sexual relationships remain poorly understood. Therefore, respondent-driven sampling was used to recruit a prospective cohort of sexually active gay, bisexual, and other men who have sex with men (MSM), aged ≥ 16 years in Vancouver, Canada. Follow-up occurred every 6 months, up to seven visits; at each visit participants reported their last sexual encounter with their five most recent partners. Stratified by self-reported HIV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
1
13
1
1
Order By: Relevance
“…Finally, a multivariable model for each relationship characteristic was constructed, which additionally adjusted for seroconcordance and partnership type, motivated by the strong associations of these partnership characteristics with condom use among MSM previously reported in the literature. 13,[15][16][17]25 Interaction terms were considered statistically significant using an alpha level of 0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a multivariable model for each relationship characteristic was constructed, which additionally adjusted for seroconcordance and partnership type, motivated by the strong associations of these partnership characteristics with condom use among MSM previously reported in the literature. 13,[15][16][17]25 Interaction terms were considered statistically significant using an alpha level of 0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…8,9 While the majority of research continues to focus on differences between individuals to explain sexual risk taking, 10 a growing body of research suggests that a significant proportion of the variability in condom use during anal intercourse exists within individuals across different sexual partnerships. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Within the sexual partnerships of MSM, the strongest associations between condom use and partnership characteristics have been observed based on partnership type and agreement of serostatus between partners (seroconcordance). Mathematical models based on data from five US cities during the 2003-2005 cycle of the National HIV Behavioral Surveillance (NHBS) System suggested that 68% of HIV transmissions among MSM occurred within main partnerships, as a result of the higher number of sex acts and lower condom use during anal sex with main partners compared to casual or exchange partners (i.e., those where money and/or other gifts were exchanged for sex).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of literature illustrates a consistent link between the use of illegal drugs (e.g., cocaine, methamphetamine, ketamine, gamma hydroxybutyrate – GHB, mephedrone, or Methyl​enedioxy​methamphetamine – MDMA/ecstasy) and an increased risk of engaging in sexual HIV transmission risk ( Kurka et al, 2015 ; Petersson et al, 2016 ). Studies utilizing both aggregate and event-level data indicate that sexual minority men who use illegal drugs (excluding marijuana in most studies) are more likely to engage in CAS with casual partners ( Card et al, 2017 ; Daskalopoulou et al, 2014 ; Rendina et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For some, prevention depends exclusively on the individual, without perceiving the context as a vulnerability factor 12 . The fact that young people, in the hour of pleasure, do not think about the consequences of unprotected sex reinforces that the question of sexual excitement cannot be underestimated when one thinks of prevention, nor other psychosocial barriers that make the use of condoms difficult, such as the consumption of alcohol and drugs 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%